1998
DOI: 10.1093/molehr/4.9.835
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the origin of redox enzymes in seminal plasma and their relationship with results of in-vitro fertilization

Abstract: Glutathione (GSH), GSH peroxidase (GPX), GSH reductase (GRD), superoxide dismutase (SOD) and catalase-like enzyme activity were quantified in seminal plasma from normozoospermic patients, men with known distal ductal occlusion, proven fathers and male partners of couples receiving in-vitro fertilization (IVF) treatment for both male and female causes. Glutathione was non-detectable (< 2.5 microM) in seminal plasma. None of the enzyme activities per unit volume were lower in semen from vasectomized men, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0
5

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 20 publications
7
31
0
5
Order By: Relevance
“…Additionally, a significant correlation between SOD activity and Zn concentration (this paper) was also stated, and this finding confirms the report of Yeung et al [43]. This correlation might be explained by the prostatic origin of SOD, especially of tissue-specific Cu-Zn from SOD [44].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, a significant correlation between SOD activity and Zn concentration (this paper) was also stated, and this finding confirms the report of Yeung et al [43]. This correlation might be explained by the prostatic origin of SOD, especially of tissue-specific Cu-Zn from SOD [44].…”
Section: Discussionsupporting
confidence: 92%
“…It was not, however, possible in this study to ascertain whether low GPX levels along the male reproductive tract are responsible for the aforementioned structural and functional abnormalities or whether the increased production of ROS by abnormal spermatozoa and the subsequent oxidative injury reduces GPX activity in seminal plasma. It has been suggested that peroxidative damage to spermatozoa may be exacerbated in assisted reproduction techniques that involve washing spermatozoa, thereby removing enzymes present in seminal plasma and then subjecting them to prolonged incubation in the absence of these potentially protective enzymes (30). In agreement with this, it has been reported that addition of an antioxidant to semen during liquefaction has a protective effect on sperm motility (34).…”
Section: Discussionmentioning
confidence: 89%
“…Although a number of studies have investigated the relationship between human seminal plasma GPX and semen parameters, results have not been consistent. Lower GPX levels have been reported among infertile men (27,28), as well as in patients with asthenozoospermia (29), while in other studies no relationship between these parameters was detected (30)(31)(32), and, surprisingly, in another study, higher levels of GPX were reported in males with oligozoospermia or asthenozoospermia (33). These discrepancies may be explained by sample sizes.…”
Section: Discussionmentioning
confidence: 92%
“…(neutral a-glucosidase, zinc, fructose) were measured at the Centre of Reproductive Medicine and Andrology, University of M€ unster with multiwell spectrophotometric assays, as previously described elsewhere (14).…”
Section: Analysis Of Seminal Plasmamentioning
confidence: 99%